2011
DOI: 10.1159/000331587
|View full text |Cite
|
Sign up to set email alerts
|

Typhlitis in Acute Childhood Leukemia

Abstract: Objective: To review our experience with typhlitis among children treated for acute leukemia. Material and Methods: The medical records of children with acute leukemia and typhlitis between 2006 and 2009 were reviewed for demographics and symptoms, and for microbiological and imaging findings. Results: In the 75 children with acute leukemia – 54 with acute lymphoblastic leukemia (ALL) and 21 with acute myeloid leukemia (AML) – there were 10 episodes of typhlitis (4.5%) that developed during 221 periods of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
2
18
1
2
Order By: Relevance
“…Acute appendicitis can, albeit rarely, be life-threatening, in particular, if overlapping with typhlitis, as seen in our cohort with one fatality and reported in the literature 2 4 . Our study shows that abdominal pain is almost always found in patients with acute appendicitis, but the method of choice for diagnosis is imaging with ultrasonography, because abdominal pain may be absent during prolonged periods of neutropenia as seen in one of our patients and anecdotally reported by others 13 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Acute appendicitis can, albeit rarely, be life-threatening, in particular, if overlapping with typhlitis, as seen in our cohort with one fatality and reported in the literature 2 4 . Our study shows that abdominal pain is almost always found in patients with acute appendicitis, but the method of choice for diagnosis is imaging with ultrasonography, because abdominal pain may be absent during prolonged periods of neutropenia as seen in one of our patients and anecdotally reported by others 13 .…”
Section: Discussionsupporting
confidence: 73%
“…Acute appendicitis is a rare infectious gastrointestinal complication in children and adolescents undergoing anti-cancer polychemotherapy or allogeneic hematopoietic stem cell transplantation (HSCT) 1 . It may occur either alone or overlap with acute typhlitis, which is defined by the triad of neutropenia, abdominal pain and fever, as well as a thickness of the bowel wall of ≥ 0.3 cm 2 6 . Appendicitis is an inflammation of the appendix, which leads to an increased diameter of the organ to ≥ 0.6 cm and corresponding clinical signs.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal X-ray may show small nonspecific signs such as bowel obstruction, a paucity of gas in the right lower quadrant, or a dilated and fluid-filled cecum. It can also show free intraperitoneal air, a complication of bowel perforation [ 3 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 On ultrasound, thickened bowel wall appears echogenic and heterogeneous due to edema, necrosis, and/or hemorrhage. 22,23 Bowel wall thickness of > 4 mm involving a bowel segment longer than 30 mm has been proposed as a diagnostic criterion for typhlitis. 17 Pericolonic fat stranding, ascites, as well as pneumatosis may also be present.…”
Section: Gastrointestinal and Liver Infectionsmentioning
confidence: 99%